Tronkvoël: An exploration of the intersection of personal experiences and identities, concerning depression - Kramer, Brunn David (Rhodes University, Faculty of Humanities, Department of Fine Art)
My diagnosis of Major Depressive Disorder in 2018 led to my experience of a terrible loneliness and a peculiar isolation that triggered a feeling of imprisonment. The work thus engages with the idea of prison as a metaphor for depression, and is influenced by earlier work that centred around prisons and ex-prisoners. I explore the intersection of gender-based issues, homophobia, racism and religious prejudice that is based on my experiences and identities, in an attempt to understand the depression and communicate the complex prejudices I face in my daily life. The work is based on my lived experience, through which depression can feel like a self-constructed prison. Thus, by visually communicating my lived experiences with depression as a coloured, queer body, I also aim to encourage dialogue and open up conversations around mental illness, as it is all too is often seen as taboo, particularly in communities of colour. I harness old family photographs as a departure point to investigate personal memory, as well as recently captured selfies to explore my narrative of self-imprisonment. I also integrate objects from childhood games such as glass marbles, with prison objects like paper mache dice and shivs all presented in the form of an installation. My invisible prison is visually communicated further through incorporating visual language of the prison "“ including tattoos, prison slang, and 'shifts and shanks' (makeshift weapons). I use a variety of mediums, including charcoal, photographic transfers, paint and linocuts, with a combination of burning and smoking techniques, made by using candle soot, as a primary feature throughout my work. In this mini-thesis I reflect on memories from my childhood and the way they have informed my experience of depression as a self-constructed prison. I position my practice in relation to the work of South African artist Tsoku Maela who navigates similar concerns in his own artworks.
Keywords: Mental illness in art; Art, -- South African 21st century; Metaphor in art; Depression, Mental; Prisons in art; Identity (Philosophical concept) in art; Gender identity in art; Intersectionality (Sociology)